Pelaksanaan Pemungutan Pajak Penghasilan Bagi Usaha Mikro Kelas Menengah berdasarkan Peraturan Pemerintah Nomor 23 Tahun 2018 di Kota Surakarta - Dian Fathri Wardana; Wida Astuti (Jurnal Discretie, 2020)
This study aims to determine the implementation of tax collection for micro and middle-class businesses based on Government Regulation Number 23 of 2018 in the City of Surakarta. This research is a descriptive empirical legal research. The primary data includes data from direct interpretation in the field. The data collection techniques used are interviews and literature study, research instruments in the form of data from interviews and Government Regulation Number 23 of 2018, then the technical analysis used was the deductive method. The results showed that the implementation of Income Tax collection for Middle Class Micro Businesses in Surakarta has increased although it is not optimal. Changes in income tax rates for MSMEs based on Government Regulation Number 23 of 2018 affect the compliance of MSME taxpayers. The ease of paying taxes has no effect on the compliance of UMKM taxpayers because there is still not even socialization of changes in tax rates. The implementation of Government Regulation Number 23 of 2018 is quite good with increasing tax revenues after the change in tax rates takes effect.